富硒生物活性肽的制备、生物活性及构效关系研究进展 "Progress on the preparation, bioactivity and structure-activity relationship of selenium-enriched bioactive peptides" - 侯春艳，杨趁仙 HOU Chunyan, YANG Chenxian (Zhongguo youzhi)
硒是人体必需的微量营养元素之一，对人体的生命活动非常重要。旨在为富硒生物活性肽的研究和应用提供理论依据，总结了富硒生物活性肽的原料来源、制备方法、生物活性，并对硒与肽的结合方式以及富硒生物活性肽的构效关系等研究进展进行了阐述。富硒生物活性肽的原料主要来源于生物载体转化，主要有植物来源、动物来源及微生物来源；通过酶解法、微生物发酵法等可制备富硒生物活性肽，其具有抗氧化、抗疲劳、降血压、抗炎等多种生物活性；富硒生物活性肽的生物活性是硒、肽共同作用的结果，与氨基酸的排列序列、空间结构、相互作用力等有密切的联系，其构效关系有待进一步研究。 Selenium is an essential trace nutritional element that is very important for human life activities. Aiming to provide a theoretical basis for the research and application of selenium-enriched bioactive peptides, the raw material sources, preparation methods, bioactivities of selenium-enriched bioactive peptides were summarized. The research progress on selenium and peptides binding modes as well as the structure-activity relationship of selenium-enriched bioactive peptides were elaborated. The raw materials of selenium-enriched bioactive peptides mainly come from the transformation of biocarriers, such as plant sources, animal sources, and microbial sources.The selenium-enriched bioactive peptides can be prepared by enzymatic hydrolysis and microbial fermentation methods, which have a wide range of bioactivities, such as antioxidant, anti-fatigue, blood pressure lowering, anti-inflammatory, and so on. The bioactivities of selenium-enriched bioactive peptides are the results of the joint action of selenium and peptides, which are closely related to the sequence, spatial structure and interaction force of amino acids, but their structure-activity relationships need to be further studied.